Research priorities for grassland science in the Eastern Mediterranean Region - Kyriazopoulos A.P. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Grasslands and rangelands have long been solely considered as a place for livestock grazing with no regard to the many other ecosystem goods and services that they provide. Mismanagement affects significantly the forage production and the biodiversity in the Mediterranean grasslands. The study of functional traits of plant species related to their response to grazing or other agronomic practices could contribute to the further understanding of various management effects on these ecosystems. For the appropriate management techniques to be applied, the multifunctionality of these ecosystems and the climatic change should be taken into account.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)